Design, preparation and pharmacodynamics of ICG-Fe(Ⅲ) based HCPT nanocrystals against cancer - Qiongzhe Ren; Xuefeng Tang; Yi Lu; Qing Li; Zhiqian Liao; Shinan Jiang; Haoli Zhang; Zhigang Xu; Lei Luo (Elsevier, 2022)
The use of nanocrystal technology to manufacture drug delivery systems intended to enhance therapeutic efficacy has attracted the attention of the pharmaceutical industry. However, the clinical application of nanocrystal drugs for injection is restricted by Ostwald ripening and the large-scale use of stabilizers such as polysorbate and lecithin, which have potential toxicity risks including hemolysis and allergies. Here, we designed an amorphous nanocrystal drug complex (IHNC), which is stabilizer-free and composed of indocyanine green (ICG) framework loading with a chemotherapeutic agent of 10-hydroxycamptothecin (HCPT). Considering the possibility of industrial manufacturing, IHNC was simply prepared with the assistance of ferric ion (III) via supramolecular assembly strategy. The theoretical result of Materials Studio simulation indicated that the prepared ICG-Fe(III) framework showed a stable spherical structure with the appropriate cavity for encapsulating the two drugs of HCPT and ICG with equal mass ratio. The IHNC was stable at physiological pH, with excellent PTT/PDT efficacy, and in vivo probing characteristics. The nanoscale size and reductive stimuli-responsiveness can be conducive to drug accumulation into the tumor site and rapid unloading of cargo. Moreover, such combination therapy showed synergistic photo/chemotherapy effect against 4T1 breast cancer and its tumor inhibition rate even up to 79.4%. These findings demonstrated that the nanocrystal drug delivery strategy could avoid the use of stabilizers and provide a new strategy for drug delivery for combination therapy.